THE LANGUAGE OF INFORMALITY WITHIN ELT CONTEXT - Jumanto Jumanto (Universitas Putera Batam, 2021)
This research paper explores aspects of informality in the English language, the target hearers referred to by the aspects, and the functions the aspects convey in verbal interactions or communication, and its contribution to English Language Teaching (ELT) in the world. The research data are retrieved, obtained, and verified from informal-English-affiliated URLs or Websites, i.e. Web-Data as sources of informal English. As the findings, informal English involves the notorious, casual, heteregeneous, inconsistent, irregular, unorganized, incomplete, shorter, cut-down, reversed-up, and speaker-dependent aspects, and has the direct and literal nature. Informal English with its relatively any topics, personal and private, is used for close people to confirm their in-group solidarity or membership of a social group within relaxed situations and unofficial contexts. Knowledge and practices of informal English are necessary for teachers as well as learners. ELT teachers should include informal English in their teaching-syllabus material with particularly-set circumstances. Learning the knowledge and practices of informal English through ELT classrooms should prevent English learners from uncontrolled learning exposures to various informal morally-dangerous settings. This way will expectedly encourage English learners to be alert and careful in using informal English, hence encouraging them to maintain interpersonal and social harmony to some broader extent.